TEACHERS’ REPORTED BELIEFS ABOUT TEACHING, KNOWLEDGE, AND STUDENT’S ABILITY: CASE STUDIES OF FOUR SENIOR HIGH SCHOOL TEACHERS IN PALEMBANG, SOUTH-SUMATERA, INDONESIA - Hanni Yukamana (Esteem Journal of English Education Study Programme, 2024)
This study aimed to explore teachers’ beliefs about teaching, knowledge (epistemic beliefs), and student’s ability. This was the first part of the study investigated the role of teachers’ beliefs in the implementation of curriculum reform in the Indonesian education system context. This study looked specifically into three kinds of teachers' beliefs which were essential in the preparation of teaching in the context of policy reform. The investigation was approached through multiple case study methodology by selecting four senior high school teachers from different public schools. Data were gathered from interviews. The result revealed that four participating teachers shared similar views about the nature of knowledge and students’ abilities. Nevertheless, beliefs about teaching were varied among individual participants. Two of the four teacher participants believed in student-centered instructional models, which were categorized into teaching beliefs that supported curriculum reform. Nevertheless, the other two participating teachers’ self-reported beliefs about teaching were situated between student-centered instructional learning and teacher-centered instructional learning models. They seemed to value both instructional learning models. Their teaching beliefs about teaching could not be categorized into beliefs that supported or inhibited the reform.